Cost Minimization Policy for Manufacturer in a Supply Chain Management System with Two Rates of Production under Inflationary Condition - Sujata Saha; Tripti Chakrabarti (Jurnal Teknik Industri, 2020)
This article presents a production inventory model for deteriorating goods with two different rates of production. The manufacturer starts manufacturing the items at a lower rate to avoid a huge investment at the initial stage and reduce the products' holding cost. However, when the stock level reaches a prefixed level, he switches on to a higher production rate to avoid shortage caused by an insufficient stock of the items. Moreover, the impact of inflation and the time value of money on the manufacturing system’s cost is considered here, which harms any business by reducing the value of an investment with time. We determined the optimum production times at both the low and high production rates by minimizing the system's total cost. Numerical examples illustrated the applicability of this proposed model. Sensitivity analysis studied the effect of changes in the parameters associated with this model on the optimal decision variables. This numerical experiment was done in LINGO 18.0 software. Results showed that the production strategy taken by the manufacturer helped reduce his total cost.